How responsive is poverty to growth? A regional analysis of poverty, inequality, and growth in Indonesia, 1984 - 99 - Jed Friedman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper uses six nationally representative household consumption surveys to develop successive poverty profiles for Indonesia over a fifteen-year period of sustained high growth followed by rapid contraction. Adopting a `cost-of-basic-needs' approach to poverty determination (an approach particularly suited to measures of absolute poverty), this paper develops price indices and calculates poverty lines from unit value data, an oft neglected source of information. The summary findings confirm that Indonesia has witnessed broadbased gains in poverty reduction over the period 1984-96 and then a dramatic reversal during the recent financial crisis. These summary findings, however, mask substantial diversity in growth, inequality, and poverty change across Indonesian regions and so subsequent analysis focuses on the links between growth, inequality, and changes in poverty at the regional level. As opposed to previous studies of poverty change that have used short panels of cross-national data to identify the relationship between growth and poverty, this study employs a longer panel for a single country in order to investigate how poverty change at the provincial level varies with province growth rates and province changes in inequality (while controlling for time invariant province characteristics). The results indicate that poverty change is highly responsive to overall growth. However closer analysis reveals that regional differences in poverty levels persist even after controlling for the effects of provincial income levels, particularly for rural areas. These findings suggest that local factors play an important role in poverty determination and may interact with growth to impact poverty reduction in differing ways across Indonesia. Future investigations will need to take a more careful look at these local determinants of poverty change and attempt to identify the types of growth toward which poverty measures are particularly responsive. – poverty ; growth ; inequality ; Indonesia.
Keywords: I32; O12; O53; R11; 330; Armut; Räumliche Verteilung; Regionale Einkommensverteilung; Regionales Wachstum; Indonesien